Letter from George Washington to Henry Knox (Nov. 30, 1780), in The Writings of George Washington from the Original Manuscript Sources 1745-1799 (John C. Fitzpatrick, ed.) - (:unkn) unknown (General Publisher, 1780)
An order to repair and prove old arms before delivery.
--
Keywords: TRANSFER